Sedimentary and rock magnetic signatures and event scenarios of deglacial outburst floods from the Laurentian Channel Ice Stream. (15th April 2018) - Leng, Wei; von Dobeneck, Tilo; Bergmann, Fenna; Just, Janna; Mulitza, Stefan; Chiessi, Cristiano M.; St-Onge, Guillaume; Piper, David J.W.
Abstract: Eastern Canadian margin sediments bear testimony to several catastrophic deglacial meltwater discharges from the retreating Laurentide Ice Sheet. The reddish-brown plumite layers deposited on the levees of the Laurentian Fan valleys have been recognized as indications of multiple outburst floods between Heinrich events 2 and 1. Five event layers have been consistently recorded in three new gravity cores retrieved on the SW Grand Banks slope and comply with the previously published Laurentian Fan core MD95-2029. The apparently huge extent of these outburst plumes around the Laurentian Fan as well as their causes and consequences are investigated in this study using physical properties, rock magnetic and grain-size analyses, together with seismoacoustic profiling. We provide the first detailed 14 C ages of the outburst event sequence and discuss their recurrence intervals in the context of regional ice retreat. Compared to the hemipelagic interlayers, event layers have overall uniform and systematic changes of rock-magnetic properties. Hematite contents increase over time and proximally while magnetite grain sizes fine upwards and spatially away from the fan. Based on the sediment composition and load, we argue that these plumites were formed by recurrent erosion of glacial mud deposits in the Laurentian Channel by meltwater outbursts. Three alternative glaciological scenarios are evaluated: in each case, the provenance of the transported sediment is not an indicator of the precise source of the meltwater. Highlights: 4 cores with consistent marine records of 5 major deglacial Laurentian outburst floods. 14 C event ages (22.0, 21.6, 19.5, 18.1, 17.9 cal ka) of two dated records conform. Hyperpycnal plumes reached 150 km off-channel and 1850 m up Grand Banks Slope. Plumite composition implies recurrent outwash from Laurentian Channel depocenter.